(untitled) (World Bulletin of Social Sciences, 2023)
In this study, the object of the study were fibers consisting of 100% wool and silk fibers, the degree of whiteness of the wool fiber was 36.6%, the silk fiber was 40.8%. For staining, natural indigo dye was used, obtained by extracting the plant Indigofera tinctoria L., and Al2(SO4)3 was used as a mordant. Dyeing of protein fibers was carried out in the following technological sequence: samples of woolen and silk fibers that underwent the process of preparation for finishing were treated in a 3-10% indigo solution containing 2.5 g/l Al2(SO4)3 at a temperature of 90-950C for 60 minutes. Then 3% acetic acid was added to the solution and the process was continued at this temperature for 10 minutes. The color characteristics of indigo-dyed protein fibers were determined on a laboratory colorimeter under standard D65 irradiation. To systematize color characteristics, a system of color circles is used and the L.a.b. color model was used. Geographic coordinates - L*, a* and b* Color values such as latitude, longitude and altitude provide information about where the color is located and about it. The L* coordinate indicates the brightness of the color, C* - color saturation, h - chromaticity, a* - the presence of red or green, b* - the presence of yellow and blue. The color qualities of all samples were determined at a wavelength of 360 nm. Experiments have shown that in the process of dyeing natural fibers with natural indigo dye, a certain type of mordant is used to create a lasting color, and by changing the concentration of the dye in the dye solution, blue colors of different colors can be obtained using one dye.